DIRECTIONS FOR THE DEVELOPMENT OF COASTAL AREA INFRASTRUCTURE IN NATAL SUB-DISTRICT, MANDAILING NATAL REGENCY, INDONESIA - Muhammad Aris; Cut Nuraini; Feby Milanie (International Journal on Livable Space, 2024)
The study highlights the critical need for infrastructure development in coastal areas to support the fisheries sector and services trade. Through various methods such as assessment of current conditions and literature review, it's clear that improving infrastructure is a top priority.Objectives: This study aims to identify the infrastructure that supports the development of coastal areas in Natal Sub-district, Mandailing Natal Regency, North Sumatera, IndonesiaMethodology and Results: The research methods include descriptive analysis to identify existing infrastructure and importance-performance analysis to evaluate the importance and performance of infrastructure.The study results show that the infrastructure is divided according to its level of importance. First, within Quadrant I, infrastructure such as fish auction sites (TPI), village unit cooperatives (KUD), cold storage, and ice factories in the Natal coastal region stand out as the main focus. Recommendations include the revitalization of TPI and KUD, and the construction of cold storage facilities. Second, in Quadrant II, infrastructure such as transport support facilities, waste management, and sanitation require attention to maintain their performance. Third, in Quadrant III, gas station facilities in Sikara Kara Village are of medium-to-low priority. Finally, in Quadrant IV, infrastructure such as waste and drainage systems need to be reviewed. The revitalization of the Setia Karya dumpsite and the construction of a drainage system are part of the recommendations to improve Natal's coastal environment.Conclusion, Significance and implications: The improvement of coastal area infrastructure in Natal Sub-District, Mandailing Natal Regency, Indonesia emphasizes on addition, repair and revitalization. It is also recommended to strengthen the involvement of local and village governments in collaborative efforts. Further studies are needed, particularly on effective implementation of infrastructure development in the same research area.